The trajectory of obesity in a cohort of Irish children and their mothers: An application of sequence analysis - David Madden (University College Dublin, UCD School of Economics, 2024)
Sequence and cluster analysis is applied to measures of body mass index for mothers and children for four waves of the Growing up in Ireland longitudinal data set. Optimal matching analysis is used to construct a dissimilarity matrix to which cluster analysis is then applied. Distinct clusterings are found for both mothers and children and multinomial logit models are then used to investigate statistical association of covariates with membership of each group. Associations are found for maternal education and diet, and child exercise. There is no correlation between membership of groups for mothers and children.
Keywords: I12; C33; C38; 330; Obesity; sequence analysis; cluster analysis